Economic Hardships During the Covid-19 Pandemic: Semiotic Analysis of the Film “Happy Girls Don’t Cry" - Subekti, Rily Khansta; Ihsan, Alfian; Dadan, Sulyana; Dasuki, Niken Paramarti (JUSS (Jurnal Sosial Soedirman), 2025)
The COVID-19 pandemic has impacted various aspects of life. Beyond the health sector, the pandemic has also caused significant economic downturns. This study aims to examine the struggles of poor families during the pandemic as represented in the film “Happy Girls Don’t Cry”. This research employs a qualitative method with Roland Barthes' semiotic approach. This approach is used to interpret the hidden meanings behind signs. It was found three scenes that represent the struggles of poor families. First, loan sharks as a practical solution in facing economic difficulties. Second, the commodification of poverty on social media. Third, selling valuable items to survive. The film represented the struggles of the lower-class society to survive during the pandemic.